2015
DOI: 10.7314/apjcp.2014.15.23.10433
|View full text |Cite
|
Sign up to set email alerts
|

New Haplotypes of the ATP Synthase Subunit 6 Gene of Mitochondrial DNA are Associated with Acute Lymphoblastic Leukemia in Saudi Arabia

Abstract: Background: Acute lymphoblastic leukemia (ALL) is the most common cancer diagnosed in children and represents approximately 25% of cancer diagnoses among those younger than 15 years of age. Aim and Objectives: This study investigated substitutions in the ATP synthase subunit 6 gene of mitochondrial DNA (mtDNA) as a potential diagnostic biomarker for early detection and diagnosis of acute lymphoblastic leukemia. Based on mtDNA from 23 subjects diagnosed with acute lymphoblastic leukemia, approximately 465 bp of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 19 publications
0
8
1
Order By: Relevance
“…Haplogroups reflect specific ancestral populations and are the result of sequential accumulation of mitochondrial mutations through maternal lineages; hence, they present continent-specific distributions. The molecular mechanisms underlying the association between mtDNA haplogroups and cancer development remains unclear and controversial results between populations have been reported (65)(66)(67)(68)(69)(70)(71)(72)(73). However, specific mtDNA haplogroups have been associated with the risk of prostate cancer, BC, CC, nasopharyngeal cancer, gastric cancer, myelodysplastic syndromes (MS), acute lymphoblastic leukemia, etc.…”
Section: Mitochondria Variants and Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Haplogroups reflect specific ancestral populations and are the result of sequential accumulation of mitochondrial mutations through maternal lineages; hence, they present continent-specific distributions. The molecular mechanisms underlying the association between mtDNA haplogroups and cancer development remains unclear and controversial results between populations have been reported (65)(66)(67)(68)(69)(70)(71)(72)(73). However, specific mtDNA haplogroups have been associated with the risk of prostate cancer, BC, CC, nasopharyngeal cancer, gastric cancer, myelodysplastic syndromes (MS), acute lymphoblastic leukemia, etc.…”
Section: Mitochondria Variants and Cancermentioning
confidence: 99%
“…However, specific mtDNA haplogroups have been associated with the risk of prostate cancer, BC, CC, nasopharyngeal cancer, gastric cancer, myelodysplastic syndromes (MS), acute lymphoblastic leukemia, etc. (65)(66)(67)(68)(69)(70)(71)(72)74). For example, an over-representation of haplogroup I in Polish cancer patients has been reported (75), haplogroup U has been shown to be associated with an increased risk of developing renal and prostate cancers (65), and haplogroup JT has been shown to be associated with MS susceptibility in North American caucasion subjects (70).…”
Section: Mitochondria Variants and Cancermentioning
confidence: 99%
“…In another study, somatic mutations in the D-loop were identified in a cohort of Chinese squamous cell carcinomas, but they did not correlate with prognosis or survival [217]. There are also D-Loop mutations in acute lymphoblastic leukemia (ALL) cases, with 89 G insertions, 95 G insertions, 182 C/T substitutions, 308 C insertions, and 311 C insertions, making a total of 132 mutations at 25 locations [397]. In a comprehensive study involving 54 hepatocellular carcinomas, 31 gastric cancers, 31 lung cancers, and 25 colorectal cancers, the incidence of somatic D-loop mutations in cancers of later stages was higher than that of early-stage cancers [203].…”
Section: Disparities At the Mitochondrial Genome Level And Their Rmentioning
confidence: 99%
“…As the main cytotoxic component of HAMLET is the oleic acid rather than the protein, the binding of HAMLET protein to ATP synthase protein subunits is likely a result of the unfolded HAMLET protein, no longer partially folded around its oleic acid cargo, binding to the ATP synthase subunits that are in proximity to HAMLET and are themselves now dissociated. Mutations in ATP synthase subunits are associated with some cancers (137)(138)(139).…”
Section: Binding To Nucleotide-binding Proteinsmentioning
confidence: 99%